Pemerolehan Bahasa Kanak-Kanak Akibat Pengaruh Film Kartun: Suatu Tinjauan Psikolinguistik - Lady Diana Yusri; Titin Ritmi (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
The children language aacquisition is influenced by the surrounding environment. The data were collected from preschool children. The conclusion of the research is children learned things beyond vocabulary and grammar. They are able to use language in many social contexts. The movies, which they watch, also influence their language acquisition. It can be seen from the use of words, phrases, and sentences from movies. Then, they imitate the words, phrases, and sentences in it. In addition, the child also may generalize of it. It is because of their limitations.